A comprehensive integrated macroseismic dataset from multiple earthquake studies - A. Tertulliani; A. Antonucci; F. Bernardini; V. Castelli; E. Ercolani; L. Graziani; A. Maramai; M. Orlando; M. Orlando; A. Rossi; T. Tuvè (Earth System Science Data)
Each Italian earthquake included in the Italian Parametric Catalogue (CPTI) is based on a single study, with its database stored in the Italian Macroseismic Database (DBMI). The DBMI contains macroseismic-intensity data for approximately 5000 Italian earthquakes. However, for the same events, numerous studies have been independently carried out over the years, with the data of such studies not having been incorporated into the DBMI. By consolidating all available data for each event, it is possible to significantly enhance the dataset used for hazard assessments and the reconstruction of local seismic histories. This approach would make studies of individual events much more robust and comprehensive. The objective of this work is to propose the integration of different macroseismic datasets for individual events by identifying criteria that can effectively merge a large number of intensity data points.